Biokinetics of 13C in the human body after oral administration of 13C-labeled glucose as an index for the biokinetics of 14C. (27th July 2016) - Masuda, Tsuyoshi; Tako, Yasuhiro; Matsushita, Kensaku; Takeda, Hiroshi; Endo, Masahiro; Nakamura, Yuji; Hisamatsu, Shun'ichi
Abstract: The retention of 13 C in the human body after oral administration of 13 C-labeled glucose was studied in three healthy volunteer subjects to estimate the 50 year cumulative body burden for 13 C as an index of the committed dose of the radioisotope 14 C. After administration of 13 C-labeled glucose, the volunteers ingested controlled diets with a fixed number of calories for 112 d. Samples of breath and urine were collected up to 112 d after administration. Samples of feces were collected up to 14 d after administration. Hair samples were obtained at 119 d after administration and analyzed as a representative index of the rate of excretion of organic 13 C via pathways such as skin cell exfoliation and mucus secretion. All samples were analyzed for 13 C/ 12 C atomic ratio to determine the rate of excretion via each pathway. We then constructed a metabolic model with a total of four pathways (breath, urine, feces, and other) comprising seven compartments. We determined the values of the biokinetic parameters in the model by using the obtained excretion data. From 74% to 94% of the 13 C administered was excreted in breath, whereas <2% was excreted in urine and feces. In the other pathway, the excretion rate constant in the compartment with the longest residence time stretched to hundreds of days but the rate constant for each subject was not statistically significant ( P value > 0.1). In addition, the dataset for one of the three subjects was markedly different from those of the other two. When we estimated the 50 year cumulative body burden for 13 C by using our model and we included non-statistically significant parameters, a considerable cumulative body burden was found in the compartments excreting to the other pathway. Although our results on the cumulative body burden of 13 C from orally administered carbon as glucose were inconclusive, we found that the compartments excreting to the other pathway had a markedly long residence time and therefore should be studied further to clarify the fate of carbon in the human body. In addition to excreta, data for serum and blood cell samples were also collected from the subjects to examine the metabolism of 13 C in human body.